2015
DOI: 10.3233/bd-150408
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy associated breast cancer (PABC): Aspects in diagnosis

Abstract: Diagnosis of a clinical entity like pregnancy associated breast cancer (PABC) is as demanding and challenging as its rarity. Increasing incidence and controversy that exists in the literature upon prognosis, tumor aggressiveness and underlying mechanisms, highlight the importance of optimizing the diagnostic strategy in women with PABC. Adjustment of standard approach for breast cancer by modifying management methods and options plays key role in decision making. Knowledge of diagnostic modalities and their li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 69 publications
1
27
0
Order By: Relevance
“…In the literature, malignant masses are usually described as predominantly hypoechoic lesions with an irregular shape and ill-defined margins [15,16,17]. Posterior acoustic enhancement, which is usually seen in benign lesions, is also reported as a sonographic finding of pregnancy-associated breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, malignant masses are usually described as predominantly hypoechoic lesions with an irregular shape and ill-defined margins [15,16,17]. Posterior acoustic enhancement, which is usually seen in benign lesions, is also reported as a sonographic finding of pregnancy-associated breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy-associated breast cancer usually presents with a palpable mass that is larger and in a more advanced stage than those seen in non-pregnant or non-lactating patients [5,7]. It has been reported that the frequency is approximately 1 in 3,000 pregnancies, but due to the increasing trend for women to delay motherhood, the frequency of this cancer will probably increase in the next years [15]. In our study group, pregnancy-associated breast cancer was found at a rate of 3.9%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multidisciplinary management of women with breast cancer in pregnancy is mandatory for its complex entity and ambiguous prognosis. Physiologic pregnancy-associated breast changes, including engorgement, hypertrophy and nipple discharge, obscure detection, make physical examination more difficult as pregnancy advances, until they steadily revert to pre-pregnancy state approximately three months after breastfeeding cessation[9]. On physical examination, breast cancer in pregnancy typically presents as a palpable painless lump.…”
Section: Discussionmentioning
confidence: 99%
“…It can be performed at any time since it does not have ionizing radiation or require the use of contrast, and has a sensitivity of 87-100% for the diagnosis of breast lesions (1,(3)(4)(5) . Although there is no consensus in the literature, some authors indicate ultrasound for pregnant or lactating patients who have palpable nodules for more than two weeks (8,9) or associated with spontaneous bloody nipple discharge (10) .…”
Section: Imaging Methods Ultrasonographymentioning
confidence: 99%